Antinociceptive effect of the essential oil of Zingiber zerumbet in mice : possible mechanisms - Khalid, Mohamed Hanief; Akhtar, Muhammad Nadeem; Tengku Mohamad, Tengku Azam Shah; Perimal, Enoch Kumar; Omar Farouk, Ahmad Akira; Israf Ali, Daud Ahmad; Lajis, Md. Nordin; Sulaiman, Mohd Roslan (Elsevier, 2011)
Abstract Ethnopharmacological relevance Zingiber zerumbet (L.) Smith, a wild edible ginger species or locally known as “lempoyang”, commonly used in the Malays traditional medicine as an appetizer or to treat stomachache, toothache, muscle sprain and as a cure for swelling sores and cuts.